Synthesis of pyrazole, 1,3-dithiolan and thiophene derivatives pendant to thiazolo[2,3-c]-1,2,4-triazole moiety - Sayed, Samia Mohamed; Khalil, Mohamed Ali; Raslan, Mohamed Abd-Elmonem (European Journal of Chemistry, 2014)
Coupling of 5-acetyl-2-amino-4-methylthaizole diazonium sulphate (1) with 3-chloro-pentane-2,4-dione (2) afforded the thiazolo[2,3-c]-1,2,4-triazole derivative, (5). Bormination of compound (5) followed by reaction with potassium cyanide afforded bis-3-oxo-propanenitrile derivative (7) which, reacts with CS2/NaH/CH3I to afford the ketene S,S-dithioacetal, (8). Synthesis of 1,3-dithiolane (11) and thiophene (15) derivatives have been reported.